2013
DOI: 10.1007/s15010-013-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and antibiotic susceptibility of viridans streptococcal bacteremia in children with febrile neutropenia

Abstract: Severe complications of VSB in neutropenic febrile children were rare. We suggest glycopeptide use according to the results of blood culture and antibiotic susceptibility tests based on the susceptibility to cefepime and the microbiologic response to empirical antibiotic treatment not including glycopeptides in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Fifteen per cent of VGSB resulted in VSSS, which is equal to the rate of VSSS from the last British study, 2 a single-center descriptive study conducted from 1995 to 1999. The mortality rate directly attributable to VGSB of 5.6% is similar to recent data both from oncology units from the rest of the world of 1.8% to 7%, 6 8 and from larger population-based studies examining VGS in AML. 9 Research from centers with lower mortality rates excludes high-risk patients such as those undergoing HSCT, 4 relapsed patients, 5 high-risk chemotherapy regimens, or those with comorbidities such as Down syndrome.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Fifteen per cent of VGSB resulted in VSSS, which is equal to the rate of VSSS from the last British study, 2 a single-center descriptive study conducted from 1995 to 1999. The mortality rate directly attributable to VGSB of 5.6% is similar to recent data both from oncology units from the rest of the world of 1.8% to 7%, 6 8 and from larger population-based studies examining VGS in AML. 9 Research from centers with lower mortality rates excludes high-risk patients such as those undergoing HSCT, 4 relapsed patients, 5 high-risk chemotherapy regimens, or those with comorbidities such as Down syndrome.…”
Section: Discussionsupporting
confidence: 83%
“…The most frequent hematological or oncological diagnosis was relapsed ALL, whereas previous studies have found AML the most common hemato-oncology diagnosis in VGSB patients. 6 , 8 The Relapsed ALL R3 protocol was introduced in 2003; patients most frequently developed VGS during weeks 7 to 11 of the protocol. Clinicians should therefore be vigilant for the development of VGSB when patients are being treated during these weeks of this protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sources have demonstrated that our chosen identification method shows results that are similar to those obtained using other methods with regards to the genus Streptococcus [ 16 , 21 , 22 ]. However, it should also be noted that the identification of alpha-hemolytic streptococci to the species level is one of the limitations of the VITEK2 system [ 23 ].…”
Section: Discussionmentioning
confidence: 68%
“…It was noticed that the rise of penicillin resistant strains was mostly observed in the S. mitis and S. sanguinis groups, whereas the S. anginosus group remains mostly susceptible to penicillin. It was also observed that some studies disregarded the difference in antimicrobial susceptibility among species when investigating VGS bacteremia [ 16 , 17 , 18 ]. We suggest that this premise can be misleading, since our data clearly shows that there is such a difference, specifically among the resistant strains of the different species.…”
Section: Discussionmentioning
confidence: 99%